2015
DOI: 10.1016/j.aogh.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Care in Brazil

Abstract: Brazil is the fourth country in the world in number of patients with diabetes. Regardless of the diabetes type, the majority of patients do not meet other metabolic control goals. The economic burden of diabetes and its complications in Brazil is extremely high, and more effective approaches for preventions and management are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 27 publications
(55 reference statements)
1
25
1
5
Order By: Relevance
“…As in other countries, T2DM rather than type 1 DM (which accounts for approximately 5% of cases of diabetes in Brazil) constitutes the bulk of this morbidity, mortality, and costs. Moreover, although there is no systematic screening for prediabetes, it is estimated that prevalence of prediabetes in Brazil is high and increasing rapidly [14]. Simōes et al describe programs implemented by the Brazilian Ministry of Health to address this diabetes epidemic, but there is not yet evidence on the effectiveness of these interventions.…”
Section: Introductionmentioning
confidence: 99%
“…As in other countries, T2DM rather than type 1 DM (which accounts for approximately 5% of cases of diabetes in Brazil) constitutes the bulk of this morbidity, mortality, and costs. Moreover, although there is no systematic screening for prediabetes, it is estimated that prevalence of prediabetes in Brazil is high and increasing rapidly [14]. Simōes et al describe programs implemented by the Brazilian Ministry of Health to address this diabetes epidemic, but there is not yet evidence on the effectiveness of these interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The patients enrolled for diabetic retinopathy screening with a portable retinal camera adequately represent the population with DM2 treated in primary health care, characterized by the predominance of the elderly, mostly women, diabetes duration over 10 years and regular glycemic control. Arterial hypertension and dyslipidemia were the most prevalent comorbidities associated with DM [20]. We observed that patients with referable DR had higher A1c than those with DR absent or non-referable, while other clinical and demographic variables were similar.…”
Section: Discussionmentioning
confidence: 56%
“…26 In Mexico and Brazil, certain drugs are not available in public healthcare system due to the high cost, despite of some medications are subsidized by government. 27,28 In our study this is a limitation, because both national health surveys not distinguish between groups of medications. Other factor that could contribute to this relation is the adherence to the treatment.…”
Section: Discussionmentioning
confidence: 94%